Analisis Destination Brand Equity di Era New Normal - Maria Angela Diva Vilanigrum Wadyatenti (Jurnal Bisnis dan Ekonomi, 2022)
A tourism destination is an interpretation brand by their illustration of the transferability of branding principles from broader marketing disciplines to a tourism speciﬁc context. The strength of a destination brand reflects in its destination brand equity. This study develops a conceptual framework for destination brand equity that goes beyond image by adapting and expanding a multidimensional consumer-based brand equity scale for application within a tourism context. This study aims to explore the relationship between destination brand equity and destination brand awareness, destination brand image, destination perceived quality, and destination brand loyalty. This research used a quantitative approach with a self-administered survey through an online survey. The empirical results, are based on a 245 consumer survey in Indonesia. The hypothesis was tested using multiple regression with SPSS 26. The importance of destination brand image, destination perceived quality, destination brand loyalty conﬁrmed, but destination brand awareness is not confirmed in building destination brand equity. Hence, investing in resources that increase these destination brands will enhance destination brand equity.